Comparison of panoramic radiograph with cone-beam computed tomography in assessment of maxillary sinus floor and nasal floor - Vijay Kumar Bokkasam; Pavani Muddepalli; Raviraj Jayam; Sathish Babu Devaki; Aruna Pakerla; Sridevi Koduri (Wolters Kluwer Medknow Publications, 2015)
Introduction: Panoramic radiograph is frequently prescribed by dentists for implant planning and, hence, accurate assessment of anatomical structures in panoramic radiograph is of utmost importance. Aims: The aim of the present study is to know the accuracy of panoramic radiograph in assessment of relationship between maxillary sinus floor and posterior teeth roots, and the distance from alveolar crest to nasal floor by comparing it with that of cone-beam computed tomographic (CBCT) image. Materials and Methods: Panoramic and CBCT images of 30 patients were analyzed. The topographic relationship of each root of posterior teeth to the maxillary sinus floor was evaluated and classified into three classes. The distance from the peak point on maxillary alveolar crest to nasal floor was measured in panoramic radiograph as well as in CBCT image. All the measurements were made by built-in measurement tools. Results: Class 1 roots in panoramic radiograph showed high agreement (86%) with CBCT image, followed by class 0 (76%). There was a significant difference in the measurements of alveolar bone height (ABH) in the nasal floor region with a P value of 0.018. Conclusion: Panoramic radiograph is reliable in assessment of nasal floor and maxillary sinus, provided position of the patient, distortion, and the inherent magnification factor are taken into consideration.